2020
DOI: 10.1002/suco.202000103
|View full text |Cite
|
Sign up to set email alerts
|

Influence of brick dust, stone dust, and recycled fine aggregate on properties of natural and recycled aggregate concrete

Abstract: The brick, stone, and construction industries produces huge quantities of non‐biodegradable waste materials and incorporation of such waste materials in concrete eventually leads to the green and sustainable construction. The present paper study the effect of partial substitution of brick dust (BD), stone dust (SD), and recycled fine aggregate (RFA) as fine aggregate on the properties of natural aggregate concrete (NAC) and recycled aggregate concrete (RAC). In the present investigation, two groups of mixes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Most research studies have shown that replacing ordinary Portland cement (OPC) or part of it in concrete with SCMs reduces the amount of cement and the carbon emissions associated with cement production [ 8 , 9 , 10 , 11 , 12 ]. Moreover, research has shown that SCMs have both pozzolanic [ 13 , 14 ] and filler properties, which are embodied in their ability to improve the mechanical and durability properties of concrete [ 10 , 15 , 16 , 17 , 18 ]. Ongoing research is exploring various alternative waste materials as potential SCMs instead of the well-known ones such as fly ash, ground granulated blast furnace slag, and silica fume.…”
Section: Introductionmentioning
confidence: 99%
“…Most research studies have shown that replacing ordinary Portland cement (OPC) or part of it in concrete with SCMs reduces the amount of cement and the carbon emissions associated with cement production [ 8 , 9 , 10 , 11 , 12 ]. Moreover, research has shown that SCMs have both pozzolanic [ 13 , 14 ] and filler properties, which are embodied in their ability to improve the mechanical and durability properties of concrete [ 10 , 15 , 16 , 17 , 18 ]. Ongoing research is exploring various alternative waste materials as potential SCMs instead of the well-known ones such as fly ash, ground granulated blast furnace slag, and silica fume.…”
Section: Introductionmentioning
confidence: 99%
“…Recycled concrete aggregate quality is lower than normal concrete, so it uses limited up to 30% to replace natural aggregate [6]. Utilization of construction materials, wherever possible, is environmentally friendly material, and its use does not become a nuisance to the environment, which is not always significant at a low cost.…”
Section: Introductionmentioning
confidence: 99%